Biology Syllabus: Effective May 1992 - Caribbean Examinations Council (Caribbean Examinations Council, 1992)
This syllabus is designed to help students to: Develop an understanding of fundamental biological principles and concepts based upon practical and theoretical knowledge of living organisms; develop a natural curiosity about living organisms without encouraging their unnecessary disturbance and/or destruction; recognise the dynamic nature of the interrelationships between organisms and their environment; recognise the social and economic implications of biology; apply biological knowledge to everyday life situations; make accurate observations of biological material and phenomena both in the field and in the laboratory; develop an ability to record information accurately by means of clear, labelled diagrams, graphs, tables, etc.; formulate hypothesis and design and carry out experiments to test them; assess and interpret simple biological experiments and data; develop and practice problem-solving skills; develop an awareness that principles of chemistry, physics and mathematics are necessary for a proper understanding of biology; appreciate that although generalizations have predictive value, there are often exceptions to them; develop a respect for all living things and the environment.
Keywords: CXC syllabus